2001
DOI: 10.7326/0003-4819-135-2-200107170-00008
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Helical Computed Tomography in Unselected Outpatients with Suspected Pulmonary Embolism

Abstract: Helical CT should not be used alone for suspected pulmonary embolism but could replace angiography in combined strategies that include ultrasonography and lung scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
1
13

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(163 citation statements)
references
References 32 publications
5
144
1
13
Order By: Relevance
“…24 Thus, many emboli found in patients with low pretest probability actually may have been subsegmental PE that would not have been diagnosed by another radiologist. As CTPA is more accurate for diagnosing central PE, 25 clinicians should consider reviewing "positive" scans with the interpreting radiologist, especially when the pretest probability was low and the filling defects identified are in distal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…24 Thus, many emboli found in patients with low pretest probability actually may have been subsegmental PE that would not have been diagnosed by another radiologist. As CTPA is more accurate for diagnosing central PE, 25 clinicians should consider reviewing "positive" scans with the interpreting radiologist, especially when the pretest probability was low and the filling defects identified are in distal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Pourtant, la sensibilité du scanner monobarrette est imparfaite, avec jusqu'à 21 % de faux négatifs rapportés [17]. La sensibilité est particulièrement faible pour la détection d'embolies au niveau des artères segmentaires et sous-segmentaires [18,19].…”
Section: Implications Thérapeutiques : Faut-il Traiter Les Embolies Punclassified
“…Interpreting the study without factoring in the pretest probability would lead to overdiagnosis and underdiagnosis of PE: Of patients who have a high-probability V/Q scan but a low pretest probability, 44% would have angiograms negative for PE, whereas in patients with a low-probability scan but a high pretest probability, 40% would be found to have PE on angiogram (see Table 3) [13,96]. Because of these interpretive factors and because patients with preexisting lung disease often have abnormal studies, V/Q scan provides a definitive answer regarding whether or not a patient should be started on anticoagulation therapy in only 25% to 40% of cases [12].…”
Section: Ventilation-perfusion Scintigraphymentioning
confidence: 99%
“…Many investigators have questioned whether the sensitivity of CT is sufficient to rule out definitively the possibility of PE [97]. Perrier et al [12] found the sensitivity and specificity to be only 70% and 91%, whereas others have reported sensitivities of 88% to 100% with negative predictive values of 89% to 95% [98][99][100].…”
Section: Spiral Computed Tomographymentioning
confidence: 99%
See 1 more Smart Citation